Ceramic modified C / C composite material with ZrC-SiC-PyC interface layer and preparation method thereof
By constructing the ZrC-SiC-PyC interface layer on the surface of carbon fiber, the problem of poor structural stability and sharp reduction of mechanical properties of ceramic modified C/C composite materials in extreme high temperature environments is solved, and the mechanical properties of the materials are improved and structural stability guaranteed are achieved.
Patent Information
- Application Number
- CN202510074127.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-17
AI Technical Summary
The existing ceramic modified C/C composite materials have poor structural stability and sharply reduced mechanical properties in oxygen-rich extreme high temperature environments, mainly due to the corrosion of carbon fibers by ceramic melt in the RMI process, resulting in structural damage and reduced load-bearing capacity.
Using a combination of SI method and RMI method, the ZrC-SiC-PyC interface layer was constructed on the surface of the carbon fiber, and PyC was deposited by the introduction of ZrSi2 powder and chemical vapor deposition method to form an effective ceramic interface layer to reduce the possibility of carbon fiber being eroded by the ceramic melt.
It effectively improves the mechanical properties of ceramic modified C/C composite materials, increases the bending strength by 26.8%~54.9%, and relieves internal stress caused by differences in thermal expansion coefficient in extreme thermal environments to ensure the stability of the composite structure.
Smart Images

Figure CN119841658A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of ceramic modified carbon / carbon composite materials, and in particular relates to a ceramic modified C / C composite material with a ZrC-SiC-PyC interface layer and a preparation method thereof. Background Art
[0002] High temperature resistance, ablation resistance and excellent high temperature mechanical properties make carbon / carbon (C / C) composites realize significant application value in the field of aerospace vehicle development. However, due to the disadvantage of carbon materials themselves being easily oxidized, C / C composites show poor structural stability and sharp performance decline in oxygen-rich extreme high temperature environments, which seriously limits the application and development of C / C composites. To address this problem, introducing ultra-high temperature ceramic phases such as silicon carbide (SiC) and zirconium carbide (ZrC) into C / C composites, that is, preparing ultra-high temperature ceramic modified C / C composites, will effectively improve the oxidation resistance of C / C composites and greatly improve the material's ablation resistance.
[0003] At present, the commonly used ceramic modified C / C composite processes include polymer impregnation pyrolysis (PIP), chemical vapor infiltration (CVI) and reactive melt infiltration (RMI). PIP uses the self-pyrolysis reaction of ceramic organic precursors to produce ceramics, and CVI uses the chemical reaction between gas phase components to produce ceramics. The ceramic phases produced by these two methods do not react with the material of the C / C composite itself, and belong to the external introduction of ceramic phases. Reactive melt infiltration (RMI) uses the penetration of the melt in the pores and the chemical reaction between the transition elements and the carbon material to synthesize a large number of ceramic phases in situ inside the C / C composite. The literature "Zhao ZG, Li KZ, Li W, et al. Ablation behavior of C / C-ZrC-SiC composites prepared by reactive melt infiltration under oxyacetylene torch at two heat fluxes[J].Ceramics International, 2018, 44(14): 17345-17358." uses ZrSi2 as raw material and RMI process to prepare C / C-ZrC-SiC composites. After oxyacetylene ablation test, the composites have good linear ablation rate and mass ablation rate, but the mechanical properties of the composites are poor. This is because during the RMI process, the metal melt will penetrate into the C / C composite and react with the carbon matrix. The chemical reaction activity is extremely high, and the mass of the supplied metal melt is much greater than the mass of the carbon matrix, resulting in the phenomenon of complete consumption of the carbon matrix, forcing the carbon fiber to react with the metal melt. When the carbon fiber is eroded by the metal melt, the structural integrity is destroyed and the bearing capacity is impaired, which eventually leads to a significant decrease in the mechanical properties of the composite. To solve this problem, the paper "Sun Q, Zhang HF, Huang CB, et al. Fabrication of C / C-SiC-ZrB2 Ultra-High Temperature Composites through Liquid-Solid Chemical Reaction[J]. Crystals, 2021, 11(11)" first used the slurry infiltration method to introduce ZrB2 powder into the C / C composite material, and then used RMI to finally produce the C / C-ZrB2-SiC composite material. Due to the presence of ZrB2 powder, most of the carbon fibers inside the composite material were not completely corroded by the metal melt, and therefore showed better load-bearing capacity.The paper "Ye ZY, Wang YL, Xiong X, et al. Microstructure, interfacial and mechanical properties of SiC interphase modified C / C-SiC composites prepared by reactive melt infiltration[J]. Journal of the European Ceramic Society, 2024, 44(15)" used chemical vapor infiltration (CVI) to first construct a SiC interface layer on the surface of carbon fiber, and then deposited pyrolytic carbon to prepare C / C-SiC composites by RMI. The study found that the Si melt only reacted with pyrolytic carbon, and the SiC interface layer effectively prevented the melt from corroding the carbon fiber. Compared with the C / C-SiC composite without the interface layer, the bending performance of the C / C-SiC composite containing the SiC interface layer was improved by 35.69%. However, the CVI process for preparing the interface layer is complicated and costly, and there is an urgent need for a simple and low-cost process to achieve the rapid preparation of the interface layer. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to propose a ceramic modified C / C composite material with a ZrC-SiC-PyC interface layer and a preparation method thereof, and to prepare a ceramic modified C / C composite material with a ZrC-SiC-PyC interface layer by combining the SI method and the RMI method. Constructing a ceramic interface layer on the surface of carbon fiber can effectively reduce the erosion of the carbon fiber by the ceramic melt during the preparation of the ceramic modified C / C composite material by the RMI method.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In one aspect, the present invention provides a method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer, comprising the following steps: The low-density C / C composite material containing ZrSi2 powder was prepared by introducing ZrSi2 powder into the low-density C / C composite material through SI method. A low-density C / C composite material containing ZrSi2 powder is prepared into a low-density C / C composite material having a ZrC-SiC-PyC interface layer by a first RMI method; PyC was deposited on a low-density C / C composite material with a ZrC-SiC-PyC interface layer by chemical vapor deposition to obtain a low-density C / C composite material with a ZrC-SiC-PyC interface layer after PyC deposition. A ceramic-modified C / C composite material with a ZrC-SiC-PyC interface layer was then prepared by a second RMI method.
[0006] In one embodiment, the process of introducing ZrSi2 powder into the low-density C / C composite material by SI method to prepare a low-density C / C composite material containing ZrSi2 powder is as follows: The C / C composite material is immersed in ZrSi2 slurry, and then placed in a set vacuum environment of -0.09MPa for 30 minutes. After being taken out, it is rinsed and dried to obtain a low-density C / C composite material with ZrSi2 powder dispersed inside. This step is repeated 1-5 times to obtain a low-density C / C composite material containing ZrSi2 powder.
[0007] In one embodiment, the preparation method of the ZrSi2 slurry is as follows: The phenolic resin powder is added into anhydrous ethanol to prepare a phenolic resin solution; ZrSi2 powder with a particle size of 1-3 microns is added to the phenolic resin solution to prepare ZrSi2 slurry.
[0008] In one embodiment, the mass ratio of the phenolic resin powder to anhydrous ethanol is 1:10; the mass ratio of the ZrSi2 powder to the phenolic resin powder is 1:6.
[0009] In one embodiment, the process of preparing a low-density C / C composite material containing ZrSi2 powder into a low-density C / C composite material having a ZrC-SiC-PyC interface layer by a first RMI method is as follows: A low-density C / C composite material containing ZrSi2 powder is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum high-temperature graphitization furnace. Under the vacuum condition of -0.09 MPa inside the vacuum high-temperature graphitization furnace, the vacuum high-temperature graphitization furnace is heated to 2000°C at a heating rate of 5°C / min, kept warm for 2h, and then cooled to room temperature at a cooling rate of 5°C / min.
[0010] In one embodiment, the ZrC-SiC-PyC interface layer in the low-density C / C composite material having a ZrC-SiC-PyC interface layer comprises a ZrC and SiC particle phase and a PyC phase on the outside of the carbon fiber, wherein the ZrC and SiC particle phases are generated by a chemical reaction between ZrSi2 and PyC, and are uniformly coated on the surface of the PyC phase on the outside of the carbon fiber to form a ZrC-SiC-PyC interface phase with a granular texture.
[0011] In one embodiment, the process of depositing PyC onto a low-density C / C composite material having a ZrC-SiC-PyC interface layer by chemical vapor deposition is as follows: The low-density C / C composite material with a ZrC-SiC-PyC interface layer is placed in an isothermal chemical vapor deposition furnace, and the isothermal chemical vapor deposition furnace is heated to 1200° C. at a heating rate of 10° C. / h, during which argon gas is continuously introduced at a flow rate of 50 sccm; After the temperature is raised to 1200°C, natural gas is introduced into the isothermal chemical vapor deposition furnace at a flow rate of 500 sccm, and the argon flow rate is set to 1500 sccm. The furnace is kept at 1200°C for 4 to 16 hours, and then the natural gas is stopped, the argon flow rate is adjusted to 50 sccm, and the furnace is naturally cooled to room temperature to complete the deposition of PyC.
[0012] In one embodiment, the carbon fiber periphery in the low-density C / C composite material with a ZrC-SiC-PyC interface layer after the PyC deposition is respectively a PyC layer, a ZrC-SiC particle layer, and a deposited PyC layer from the inside to the outside; Among them, the deposited PyC layer will serve as an internal carbon source to provide reaction raw materials for the preparation of ceramic modified C / C composites.
[0013] In one embodiment, the process of preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer by a second RMI method is as follows: The low-density C / C composite material with a ZrC-SiC-PyC interface layer after depositing PyC is put into a graphite crucible, and the low-density C / C composite material with a ZrC-SiC-PyC interface layer after depositing PyC is completely buried with ZrSi2 powder with a particle size of 1-3 microns, and then placed in a vacuum high-temperature graphitization furnace. Under the vacuum condition of -0.09 MPa inside the vacuum high-temperature graphitization furnace, the vacuum high-temperature graphitization furnace is heated to 2000°C at a heating rate of 5°C / min, kept warm for 2h, and then cooled to room temperature at a cooling rate of 5°C / min.
[0014] Another aspect of the present invention provides a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer obtained by the above-mentioned method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer, the material comprising a C / C-ZrC-SiC composite material matrix phase and carbon fibers located inside the C / C-ZrC-SiC composite material matrix phase; The matrix phase of the C / C-ZrC-SiC composite material is a ceramic phase produced by the reaction of deposited PyC and ZrSi2.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a ceramic modified C / C composite material with a ZrC-SiC-PyC interface layer. First, the present invention prepares a ZrC-SiC-PyC interface layer in a low-density C / C composite material by a two-step method of SI and RMI. Compared with CVD and PIP methods, the method proposed by the present invention has significant advantages in operation difficulty and cost control. By adjusting the content of ZrSi2 introduced into the low-density C / C composite material by the SI method, ceramic interface layers of different thicknesses can be obtained. The surface of the ZrC-SiC-PyC interface layer prepared according to the method of the present invention is rougher than that of the ceramic interface layer prepared by the CVD method, which is conducive to achieving the interlocking effect between the interface layer and the matrix, and at the same time plays a certain guiding role in the deflection of the crack, which can increase the bonding strength between the interface and the matrix and improve the cohesion of the composite matrix. Secondly, the ZrC-SiC-PyC interface layer can effectively protect the structural integrity of the carbon fiber and improve the mechanical properties of the modified C / C composite material. Normally, when the RMI method is used to prepare ceramic modified C / C composites, the content of PyC in the low-density C / C composites cannot meet the huge chemical reaction required by the ceramic melt, resulting in the ceramic melt completely consuming PyC and reacting with the carbon fiber, destroying the original structural characteristics of the carbon fiber, and ultimately causing the carbon fiber to lose its bearing capacity, and the mechanical properties of the modified C / C composite material are seriously reduced. The construction of a ceramic interface layer on the outside of the carbon fiber mainly plays the role of preventing the ceramic melt from completely reacting with PyC, reducing the possibility of carbon fiber being eroded by the melt, and improving the mechanical properties of the ceramic modified C / C composite material. According to the results of the bending mechanics test, the bending strength of the ceramic modified C / C composite material with a ZrC-SiC-PyC interface layer is 26.8%~54.9% higher than that of the ceramic modified C / C composite material without an interface layer. Finally, the ZrC-SiC ceramic modified C / C composite material further prepared on the basis of the ZrC-SiC-PyC interface layer has a more compatible thermal expansion coefficient with the ceramic matrix compared to the single ZrC or SiC interface layer. When the modified C / C composite material is used in an extreme thermal environment, the ZrC-SiC-PyC interface layer can effectively relieve the internal stress caused by the difference in thermal expansion coefficient and ensure the stability of the composite material structure.
[0016] The present invention adopts a combination of SI method and RMI method to prepare a ceramic modified C / C composite material with a ZrC-SiC-PyC interface layer. The presence of the ceramic phase interface layer can reduce the degree of erosion of carbon fiber by ceramic melt, protect the integrity of the carbon fiber structure, and is conducive to the ceramic modified C / C composite material to show higher mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1This is a low-magnification photograph of the microscopic morphology of the ZrC-SiC-PyC interface layer; Figure 2 This is a high-magnification photo of the microscopic morphology of the ZrC-SiC-PyC interface layer; Figure 3 This is a microscopic morphology photograph of the ZrC-SiC-PyC interface layer after depositing PyC; Figure 4 This is a microscopic morphology photograph of a C / C-ZrC-SiC composite material with a ZrC-SiC-PyC interface layer. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0023] The invention relates to the technical field of preparation of ceramic modified carbon / carbon composite materials, and specifically provides a preparation method of a ceramic modified carbon / carbon (C / C) composite material having a zirconium carbide (ZrC)-silicon carbide (SiC)-pyrolytic carbon (PyC) interface layer by combining a slurry infiltration method (SI) and a reactive melt infiltration method (RMI).
[0024] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0025] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0026] This embodiment provides a method for preparing a ceramic-modified C / C composite material having a ZrC-SiC-PyC interface layer, and its technical solution will be specifically described through three embodiments.
[0027] The specific process of the above embodiment is: Step 1, preparation of ZrSi2 slurry: Ⅰ Preparation of phenolic resin solution. When preparing the phenolic resin solution, add the phenolic resin powder to the anhydrous ethanol reagent, first place it in a magnetic stirrer and stir for 5 minutes, then place it in an ultrasonic cleaning machine and ultrasonically vibrate for 30 minutes to completely dissolve the phenolic resin powder in the anhydrous ethanol reagent. Finally, a phenolic resin solution with a bright and uniform color is obtained.
[0028] The dosage of the phenolic resin powder and anhydrous ethanol is based on the mass ratio of the two, that is, phenolic resin: anhydrous ethanol = 1:10, and the ratio is the mass ratio.
[0029] Ⅱ Preparation of ZrSi2 slurry. Add ZrSi2 powder with a particle size of 1-3 microns to the above phenolic resin solution, and then place the solution in a magnetic stirrer and stir it for 3 hours to obtain ZrSi2 slurry with good dispersion.
[0030] The amount of the ZrSi2 powder is determined according to the amount of the phenolic resin powder, that is, ZrSi2 powder: phenolic resin powder = 1:6, and the ratio is a mass ratio.
[0031] Step 2: Introduce ZrSi2 powder into the low-density C / C composite material by SI method: Ⅰ Vacuum impregnation ZrSi2 slurry. 3The C / C composite material is immersed in the ZrSi2 slurry described in step 1, and then the ZrSi2 slurry containing the C / C composite material is placed in a vacuum impregnation box. The vacuum pump connected to the vacuum impregnation box is turned on to reduce the vacuum degree in the vacuum impregnation box to -0.09 MPa; after turning off the vacuum pump, the ZrSi2 slurry containing the C / C composite material is placed under a vacuum degree of -0.09 MPa for 30 minutes. Subsequently, the vacuum impregnation box is unloaded and returned to normal pressure, and the ZrSi2 slurry containing the carbon / carbon composite material is taken out.
[0032] Ⅱ Cleaning and drying the C / C composite material. Take out the C / C composite material from the ZrSi2 slurry, rinse the surface of the C / C composite material with anhydrous ethanol reagent, and remove the residual mud on the surface of the C / C composite material. Then, put the C / C composite material into a 70°C oven for drying to obtain a low-density C / C composite material with ZrSi2 powder dispersed inside.
[0033] In order to control the mass of ZrSi2 introduced into the low-density C / C composite material, the method described in step 2 needs to be repeated 1 to 5 times, and finally a low-density C / C composite material containing 15% to 50% ZrSi2 powder can be obtained, where the ratio is mass percentage.
[0034] Table 1 Parameters of each embodiment in step 2
[0035] Step 3, preparing a low-density C / C composite material with a ZrC-SiC-PyC interface layer by RMI method: The low-density C / C composite material containing ZrSi2 powder described in step 2 is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum high-temperature graphitization furnace, and the vacuum high-temperature graphitization furnace is raised to 2000°C at a rate of 5°C / min, kept warm for 2h, and then cooled to room temperature at a rate of 5°C / min. The vacuum degree in the vacuum high-temperature graphitization furnace is maintained at -0.09MPa during the heating and cooling period. After taking out the sample, a low-density C / C composite material with a ZrC-SiC-PyC interface layer is obtained.
[0036] Step 4, preparing ceramic modified C / C composite material by RMI method: Ⅰ Chemical vapor infiltration deposition of PyC: The low-density C / C composite material with a ZrC-SiC-PyC interface layer described in step 3 is placed in an isothermal chemical vapor deposition furnace, and the deposition furnace is set to heat up to 1200°C at a heating rate of 10°C / h, and argon is continuously introduced at a flow rate of 50sccm. After the deposition furnace is heated to the target temperature, natural gas is introduced into the furnace at a flow rate of 500sccm, and the argon flow rate is set to 1500sccm, so that the deposition furnace is maintained at 1200°C for 4~16h, and then the natural gas is stopped, and the argon flow rate is adjusted to 50sccm, and the deposition furnace is naturally cooled to room temperature. After taking out the sample, a low-density C / C composite material with a ZrC-SiC-PyC interface layer after depositing PyC is obtained.
[0037] Ⅱ Preparation of ceramic modified C / C composites with ZrC-SiC-PyC interface layer by RMI method: The low-density C / C composite material with a ZrC-SiC-PyC interface layer after the above-mentioned deposition of PyC is placed in a graphite crucible, and ZrSi2 powder with a particle size of 1-3 microns is laid around the C / C composite material until the C / C composite material is completely buried in the powder. Subsequently, the graphite crucible is placed in a vacuum high-temperature graphitization furnace, and the vacuum high-temperature graphitization furnace is raised to 2000°C at a rate of 5°C / min, kept warm for 2h, and then cooled to room temperature at a rate of 5°C / min. The vacuum degree in the vacuum high-temperature graphitization furnace is maintained at -0.09MPa during the heating and cooling period of the vacuum high-temperature graphitization furnace. After taking out the sample, a C / C-ZrC-SiC composite material is obtained, that is, a ceramic-modified C / C composite material with a ZrC-SiC-PyC interface layer.
[0038] Table 2 Parameters of each embodiment in step 4
[0039] The low-density C / C composite material with a ZrC-SiC-PyC interface layer was observed by scanning electron microscopy, as shown in the accompanying figure. Figure 1 and Figure 2 The ZrC-SiC-PyC interface layer contains ZrC and SiC particle phases and the PyC phase on the outside of the carbon fiber, wherein the ZrC and SiC particle phases are generated by chemical reaction between ZrSi2 and PyC and are uniformly coated on the surface of the PyC phase on the outside of the carbon fiber to form a granular ZrC-SiC-PyC interface phase. The low-density C / C composite material with a ZrC-SiC-PyC interface layer after depositing PyC was observed by scanning electron microscopy, as shown in the accompanying figure. Figure 3At this time, the ZrC-SiC-PyC interface layer structure around the carbon fiber is clearly visible, from the inside to the outside, it is respectively carbon fiber, PyC layer, ZrC-SiC particle layer, and deposited PyC layer. The deposited PyC layer will serve as an internal carbon source to provide reaction raw materials for the preparation of ceramic modified C / C composite materials. The final prepared C / C-ZrC-SiC composite material was observed by scanning electron microscopy, as shown in the accompanying figure. Figure 4 As shown. The PyC deposited in step 4 reacts with ZrSi2 to produce a large amount of ceramic phase, which becomes the matrix phase of the C / C-ZrC-SiC composite material. The carbon fiber inside the matrix phase is not eroded by the ZrSi2 melt due to the existence of the ZrC-SiC-PyC interface phase, and the integrity of the fiber structure can be maintained.
[0040] Table 3 Mechanical properties test parameters of C / C-ZrC-SiC composites prepared in various embodiments
[0041] The present invention uses the method of SI combined with RMI to quickly prepare a ceramic modified C / C composite material containing an interface layer, significantly improves the mechanical properties of the material, and broadens the engineering application scope of the ceramic modified C / C composite material.
[0042] Mechanical properties of the ceramic-modified C / C composite material having a ZrC-SiC-PyC interface layer, i.e., the C / C-ZrC-SiC composite material, prepared in each embodiment of the present invention were tested. The results showed that the flexural strength of the composite material was 90-110 MPa, which was 26.8%-54.9% higher than that of the C / C-ZrC-SiC composite material without a ZrC-SiC-PyC interface layer (flexural strength was 71 MPa).
[0043] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer, characterized in that: The following steps are involved: The low-density C / C composite material containing ZrSi2 powder was prepared by introducing ZrSi2 powder into the low-density C / C composite material through SI method. A low-density C / C composite material containing ZrSi2 powder is prepared into a low-density C / C composite material having a ZrC-SiC-PyC interface layer by a first RMI method; PyC was deposited on a low-density C / C composite material with a ZrC-SiC-PyC interface layer by chemical vapor deposition to obtain a low-density C / C composite material with a ZrC-SiC-PyC interface layer after PyC deposition. A ceramic-modified C / C composite material with a ZrC-SiC-PyC interface layer was then prepared by a second RMI method.
2. The method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 1, characterized in that: The process of introducing ZrSi2 powder into the low-density C / C composite material by SI method to prepare a low-density C / C composite material containing ZrSi2 powder is as follows: The C / C composite material is immersed in ZrSi2 slurry, and then placed in a set vacuum environment of -0.09MPa for 30 minutes. After being taken out, it is rinsed and dried to obtain a low-density C / C composite material with ZrSi2 powder dispersed inside. This step is repeated 1-5 times to obtain a low-density C / C composite material containing ZrSi2 powder.
3. The method for preparing a ceramic-modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 2, characterized in that: The preparation method of the ZrSi2 slurry is as follows: The phenolic resin powder is added into anhydrous ethanol to prepare a phenolic resin solution; ZrSi2 powder with a particle size of 1-3 microns is added to the phenolic resin solution to prepare ZrSi2 slurry.
4. The method for preparing a ceramic-modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 3, characterized in that: The mass ratio of the phenolic resin powder to anhydrous ethanol is 1:10; the mass ratio of the ZrSi2 powder to the phenolic resin powder is 1:
6.
5. The method for preparing a ceramic-modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 1, characterized in that: The process of preparing a low-density C / C composite material containing ZrSi2 powder into a low-density C / C composite material having a ZrC-SiC-PyC interface layer by the first RMI method is as follows: A low-density C / C composite material containing ZrSi2 powder is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum high-temperature graphitization furnace. Under the vacuum condition of -0.09 MPa inside the vacuum high-temperature graphitization furnace, the vacuum high-temperature graphitization furnace is heated to 2000°C at a heating rate of 5°C / min, kept warm for 2h, and then cooled to room temperature at a cooling rate of 5°C / min.
6. The method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 1, characterized in that: The ZrC-SiC-PyC interface layer in the low-density C / C composite material with a ZrC-SiC-PyC interface layer comprises a ZrC and SiC particle phase and a PyC phase on the outside of the carbon fiber, wherein the ZrC and SiC particle phases are generated by a chemical reaction between ZrSi2 and PyC, and are uniformly coated on the surface of the PyC phase on the outside of the carbon fiber to form a ZrC-SiC-PyC interface phase with a granular texture.
7. The method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 1, characterized in that: The process of depositing PyC onto a low-density C / C composite material having a ZrC-SiC-PyC interface layer by chemical vapor deposition is as follows: The low-density C / C composite material with a ZrC-SiC-PyC interface layer is placed in an isothermal chemical vapor deposition furnace, and the isothermal chemical vapor deposition furnace is heated to 1200° C. at a heating rate of 10° C. / h, during which argon gas is continuously introduced at a flow rate of 50 sccm; After the temperature is raised to 1200°C, natural gas is introduced into the isothermal chemical vapor deposition furnace at a flow rate of 500 sccm, and the argon flow rate is set to 1500 sccm. The furnace is kept at 1200°C for 4 to 16 hours, and then the natural gas is stopped, the argon flow rate is adjusted to 50 sccm, and the furnace is naturally cooled to room temperature to complete the deposition of PyC.
8. The method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 1, characterized in that: The carbon fiber peripheries in the low-density C / C composite material with a ZrC-SiC-PyC interface layer after PyC deposition are respectively a PyC layer, a ZrC-SiC particle layer, and a deposited PyC layer from the inside to the outside; Among them, the deposited PyC layer will serve as an internal carbon source to provide reaction raw materials for the preparation of ceramic modified C / C composites.
9. The method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer according to claim 1, characterized in that: The process of preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer by the second RMI method is as follows: The low-density C / C composite material with a ZrC-SiC-PyC interface layer after depositing PyC is put into a graphite crucible, and the low-density C / C composite material with a ZrC-SiC-PyC interface layer after depositing PyC is completely buried with ZrSi2 powder with a particle size of 1-3 microns, and then placed in a vacuum high-temperature graphitization furnace. Under the vacuum condition of -0.09 MPa inside the vacuum high-temperature graphitization furnace, the vacuum high-temperature graphitization furnace is heated to 2000°C at a heating rate of 5°C / min, kept warm for 2h, and then cooled to room temperature at a cooling rate of 5°C / min.
10. A ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer obtained by the method for preparing a ceramic modified C / C composite material having a ZrC-SiC-PyC interface layer according to any one of claims 1 to 9, characterized in that: It includes a C / C-ZrC-SiC composite material matrix phase and carbon fibers located inside the C / C-ZrC-SiC composite material matrix phase; The matrix phase of the C / C-ZrC-SiC composite material is a ceramic phase produced by the reaction of deposited PyC and ZrSi2.
Citation Information
Patent Citations
Preparing method of SiC-ZrC gradient modified carbon / carbon composite material
CN106045550A
Cf / C-SiC-ZrC composite material and preparation method thereof
CN110282992A
ZrB2-ZrC-SiC modified carbon / carbon composite material as well as preparation method and application thereof
CN116120080A
High-strength carbon / ceramic brake disk with ceramic functional layer
WO2024148738A1